The effect of milrinone on the intraoperative hemodynamics during off-pump coronary bypass surgery in patients with an elevated echocardiographic index of the ventricular filling pressure - Jong Wook Song (Korean Journal of Anesthesiology, 2011)
BackgroundHemodynamic derangement during off-pump coronary artery bypass surgery (OPCAB) is mainly attributed to impaired filling and diastolic dysfunction. An elevated ratio of the mitral velocity to the early-diastolic velocity of the mitral annulus (E/e' > 15) is a relatively new indicator of diastolic function, and this was reported to be associated with impaired hemodynamics during OPCAB. We investigated the efficacy of milrinone on the perioperative hemodynamics and short term outcomes of patients with an E/e' > 15 and who underwent OPCAB.MethodsThe patients were randomly allocated into either group C (control, n = 31) or group M (n = 31) and they were treated with the same amount of either normal saline or milrinone (0.5 µg/kg/min) without bolus loading after completion of internal mammary artery harvest until the end of operation. Hemodynamic measurements were recorded after the induction of anesthesia (T1), 5 min after starting each distal anastomosis of the left anterior descending artery (T2), left circumflex artery (T3) and right coronary artery (T4), and 5 min after sternum closure (T5).ResultsThe mixed venous oxygen saturation (SvO2) was lower through T2-T4 compared to the baseline value in both groups, while the degree of the decrease was significantly less in group M than that in group C. The other hemodynamic variables, the operative data and the postoperative outcomes were similar between the two groups.ConclusionsIntraoperative infusion of milrinone did not significantly improve the perioperative hemodynamics and the subsequent short term outcomes for the patients with preexisting diastolic dysfunction as represented by an elevated E/e' value, although it reduced the degree of decrease of the SvO2 during OPCAB.